Digital video creation: An alternative improving oral performance in teaching English as a Foreign Language - Đorđević, Jasmina P. (Studies in Teaching and Education, 2024)
This paper reports the findings from an action-based case study conducted with a convenience sample including 42 students encouraged by their teacher to create digital videos as an additional practice tool to improve their oral performance in English as a Foreign Language. The students recorded themselves giving a 10-minute talk following their teacher’s instructions. The comparison of the students’ oral performance between the oral exam at the end of the fourth semester and the oral exams at the end of the previous three semesters provided evidence of improvement in the students’ oral performance in the fourth semester due to the digital videos the students created. The students also completed a questionnaire focusing on their opinions about the additional tool to practice their oral performance. The analyses of the obtained results indicate a positive effect of digital videos created by students both on their oral performance as well as their attitude to digital video creation. The pedagogical implications of this study suggest three main applications of digital videos: a) practice tool to help students improve their oral performance in English, b) feedback tool to help teachers provide students with feedback on areas that need improvement and c) assessment tool to help teachers evaluate their students’ speaking skills.